Reflections and Recommendations on Undergraduate Simulations with Ethical Scenarios as a Pillar of Health Professionals Training; [Reflexions I Recomanacions Sobre Simulacions de Llicenciatura O Grau Amb Escenaris Ètics Com a Pilar de la Formació en Professionals de la Salut]; [Reflexiones y Recomendaciones Sobre Simulaciones de Licenciatura O Grado Con Escenarios Éticos Como Pilar de la Formación en Profesionales de Salud] - Navarro-Torres, R (Universitat de Barcelona, Observatorio de Bioetica y Derecho, 2025)
Objective: To propose recommendations for teaching bioethics to undergraduate students in health-related programs, based on teaching experience, and to analyze its implementation through simulation-based education. Development: In the undergraduate training of health professionals, significant concerns arise regarding the teaching of ethics, emphasizing the need to prepare students to face complex ethical dilemmas in their clinical practice. Simulated scenarios with ethical themes are presented as an effective tool to address these concerns, allowing students to experience and reflect on moral situations in a controlled environment. Identifying and exploring both traditional and current ethical dilemmas in various health professions is crucial for developing meaningful learning experiences. Additionally, the applicability of the recommendations from the International Society for Simulation provides a structured guide for designing simulations on ethical topics, ensuring these experiences are relevant and effective in the ethical training of future health professionals. Conclusion: Undergraduate simulations with ethical scenarios are a fundamental pillar in the education of health professionals, preparing them to face the ethical challenges of their future clinical practice by promoting ethical competencies and critical reflection among students. © (c) 2025 Jenny Forero Villalobos, Alix Soublette Sánchez, Paulina Húmeres Flores, Katerina Castillo Valderrama, Eugenia Ruiz Vidal, Rossana Navarro Torres, Natalia Palma Vidal, Rossemarie Krebs Brahm, Soledad Armijo Rivera.